Chinese Opera : Images and Stories - Siu, Wang-Ngai, 1938- (Book collections on Project MUSE., 1997)
Chinese Opera looks at Chinese society through an exciting series of photographs of operatic performances from many regions of the country. The book introduces the reader to this unique theatrical form and tells the traditional stories that are its narrative foundation. Siu Wang-Ngai's extraordinary images, taken in existing light during performances, lovingly reveal the visual excitement of Chinese opera and point to the differences in costuming and presentation that distinguish each regional style and character type. Through Peter Lovrick's engaging text, Chinese Opera provides a brief anecdotal history of the development of Chinese opera and introduces a language of theatrical convention entirely new to the Westerner. It also identifies the hallmarks of the dozen or so regional opera styles found in this collection. As well, the book arranges the stories in a rough chain of being, from heaven, through the whole social structure on earth from emperor to outlaw, to ghosts in the nether world, offering a revealing view of Chinese social tradition and experience. Chinese opera has a rich repertoire drawn from history, legends, myths, folk tales, and classic novels. These stories are full of colourful characters and surprising turns. Chinese Opera opens a door onto the wealth of Chinese traditional drama in a way that will interest drama aficionados, admirers of theatrical photography, students of Chinese drama, those interested in the culture of China, and everyone who enjoys a lively story. It is not necessary to be knowledgeable about the dramatic tradition to sit back, like the Chinese audience of a regional opera, and enjoy a good yarn. Siu Wang-Ngai's record of opera performance makes these stories come alive.